A materialização dos modalizadores no gênero defesa de trabalho de conclusão de curso (tcc) : índices de argumentatividade - Deus, Kátia Regina Gonçalves de (2025)
In the academic field, countless genres are produced by students and teachers, which enable the inclusion and interaction of these subjects in this field of human activity, as well as the production of scientific knowledge. One of these genres is the Final Course Project Defense (FCP Defense), a formal oral text that is an integral part of many undergraduate courses. It is characterized as a public ceremony, whose purpose is to present the results of scientific research carried out by the student, who assumes the research task. Through this genre, the actors involved in this process express themselves orally, leaving linguistic elements recorded in their speeches that reveal how they behave argumentatively, assuming different positions before their interlocutor(s). Based on this comprehension, it is understood that discursive modalizers are one of the possible linguistic elements that generate argumentativeness in the discursive genre of FCP Defense. Given this, this research aims to analyze and describe the semantic- argumentative and pragmatic functioning of modalizers in the discursive genre of FCP Defense, and also to identify the effects of meaning that these modalizers generate in that genre. The theoretical framework adopted by this study is based on the Theory of Argumentation in Language (TAL), proposed by Ducrot et al. (1988), and is grounded in studies on Discursive Modality presented by Lyons (1977), Palmer (2001), Cervoni (1989), Neves (2010), Castilho and Castilho (2002), Koch (2009), Nascimento (2010), Nascimento and Silva (2012), among others, and is understood as a semantic-argumentative and pragmatic phenomenon that materializes through certain linguistic elements. Finally, the notion of “genre” is conceived based on the Theory of Discursive Genres, proposed by Bakhtin (2000 [1979]) and others, as well as the interaction process is established based on the concept of “face”, proposed by Goffman (1967), and “politeness”, presented by Brown and Levinson (1978, 1987), with the contribution of other authors. Methodologically, this research is characterized as qualitative in nature and also assumes a descriptive character based on interpretation. The study’s corpus consisted of 20 (twenty) thesis defenses, which were collected from 10 (ten) undergraduate courses at the Federal University of Paraíba (UFPB); of these defenses, which were recorded and transcribed, 6 (six) were used for cataloging and analysis occurrences of modalizers. The results obtained point to the finding that modalizers act in the process of interaction and evaluation of the genre under investigation, exposing how the speakers (active in this situation) act argumentatively, directing their discourses towards certain conclusions based on the objective they wish to achieve. Thus, in the evaluation process that constitutes the FCP Defense, the speaker's face may or may not be preserved, and the tensions expected for this communicative moment may or may not be maximized, all of which will depend on the linguistic choices made by the speakers at each moment of the Defense. In this sense, the analyses showed that certain modalizers favor the interaction process because, when used by speakers, they contribute to preserving the speakers’ face and reducing tensions, maintaining the interaction and engagement of the participants involved in this social event – especially the assertive and quasi-assertive epistemic modalizers and the deontic modalizers (those of obligation with an instructional character, those of possibility, and those of volition), as well as the evaluative modalizers (which convey a positive evaluation) and some delimiters modalizers. Such modalizers are an integral part of the semantic-argumentative and pragmatic functioning of the FCP Defense and, as a result, mark characteristic aspects of the linguistic style and the very structure of this genre.